We are human, they are not: Driving forces behind outgroup dehumanisation and the humanisation of the ingroup - Vaes, Jeroen (2013)
Mostly invigorated by infrahumanisation theory, our knowledge on processes of dehumanisation in intergroup relations has grown considerably in the last decade. Building on these earlier endeavours, the present chapter reviews some recent empirical extensions that highlight the importance of differentiating between ingroup humanisation and outgroup dehumanisation because they are often moderated by specific variables. The role of these separate processes is discussed as a function of the main structural elements that define intergroup behaviour; that is, the defining boundaries of the groups, the relation between the groups at hand, and the ideologies of its members. Finally, the role of the different senses of humanness is discussed, suggesting that the folk conception of humanness differs between cultures.